2016
DOI: 10.3892/ijo.2016.3646
|View full text |Cite
|
Sign up to set email alerts
|

SPARC overexpression combined with radiation retards angiogenesis by suppressing VEGF-A via miR-410 in human neuroblastoma cells

Abstract: Neuroblastoma (NB) is the most common extracranial solid tumor in children and despite aggressive therapy survival rates remain low. One of the contributing factors for low survival rates is aggressive tumor angiogenesis, which is known to increase due to radiation, one of the standard therapies for neuroblastoma. Therefore, targeting tumor angiogenesis can be a viable add-on therapy for the treatment of neuroblastomas. In the present study, we demonstrate that overexpression of secreted protein acidic and ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…MiR-410, a novel cancer-related microRNA, has been found to be dysregulated in cancers. 13 , 14 , 15 Li et al demonstrated that miR-410 promotes cell proliferation by targeting BRD7 in non-small cell lung cancer (NSCLC). 16 In prostate cancer, miR-410 could be served as a potential serum biomarker for the diagnosis.…”
mentioning
confidence: 99%
“…MiR-410, a novel cancer-related microRNA, has been found to be dysregulated in cancers. 13 , 14 , 15 Li et al demonstrated that miR-410 promotes cell proliferation by targeting BRD7 in non-small cell lung cancer (NSCLC). 16 In prostate cancer, miR-410 could be served as a potential serum biomarker for the diagnosis.…”
mentioning
confidence: 99%
“…In gastric cancer, Zhang et al (30) demonstrated that the suppression of angiogenesis by SPARC may be mediated by downregulating the expression of vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMP-7). Notably, overexpression of SPARC has also been demonstrated to be involved in radiation-reduced tumor angiogenesis by downregulating VEGF-A via microRNA-410 (31). The pathway that is associated with angiogenesis in retinopathy and is regulated by SPARC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both proteins significantly increased the rate and overall number of interneurons that migrated into the cortex over time ( Figure 3G). SPARC and SerpinE1 have been shown to inhibit both endothelial cell migration and proliferation (Boyineni et al, 2016;Hasselaar and Sage, 1992;Lane et al, 1994;Menashi et al, 1993).…”
Section: Resultsmentioning
confidence: 99%